2015
DOI: 10.1017/jsl.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

Undecidability of Consequence Relation in Full Non-Associative Lambek Calculus

Abstract: We prove that the consequence relation in the Full Non-associative Lambek Calculus is undecidable. An encoding of the halting problem for 2-tag systems using finitely many sequents in the language {⋅,∨} is presented. Therefore already the consequence relation in this fragment is undecidable. Moreover, the construction works even when the structural rules of exchange and contraction are added.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Immediately, it turns out that involutive full non-associative Lambek calculus (denoted by InFNL) is strongly conservative over full non-associative Lambek calculus (denoted by FNL). In conjunction with the undecidability result established by Chvalovský [6], it follows that the deducibility problem for InFNL is undecidable. Moreover, using the idea in [19], we show that the provability problem for NACCLL − is undecidable.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Immediately, it turns out that involutive full non-associative Lambek calculus (denoted by InFNL) is strongly conservative over full non-associative Lambek calculus (denoted by FNL). In conjunction with the undecidability result established by Chvalovský [6], it follows that the deducibility problem for InFNL is undecidable. Moreover, using the idea in [19], we show that the provability problem for NACCLL − is undecidable.…”
Section: Introductionmentioning
confidence: 66%
“…In view of this result, it is natural to ask how the lack of associativity of multiplication affects the decision problems for linear logic and related systems. So far, however, it has hardly been investigated whether the decision problems for non-associative versions of propositional linear logic are decidable or not, whereas several substructural logicians investigated the decision problems for various non-associative logics, see e.g., [2,4,5,6,8,9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we mention cases in which the lattice is not required to be distributive. This class of 'lattice-ordered residuated groupoids' has an undecidable universal theory [8], whereas its equational theory is in PSPACE [6]. If associativity of • is assumed, the undecidability of the universal theory is proved in [19].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an encoding of atomic conditional SRSs in RL c is shown. Roughly speaking the conditionality in rules is expressed by join and an auxiliary rewriting system (inspired by [1]), the rewriting symbol is encoded by an implication and a set of rules by a meet of encoded rules. Although the constant 1 plays also an important role in this encoding, it can be shown that it is not necessary.…”
mentioning
confidence: 99%
“…The idea of using the lattice disjunction for similar purposes comes from [14], where it is used for linear logic. In fact, our application of this idea was inspired by [3].…”
mentioning
confidence: 99%